Hope in The Holy Quran: exegetical study - Moutan, Mousa Mahmoud (Arab Journal for Sciences and Research Publishing, 2022)
This research deals with one of the methods of Quranic interpretation, known as al- Mawdu’iy Method (Thematic Interpretation), and is based on a thematic analysis of the Qur’anic term “ Rajaa’ ” (Hope) in the Quran. In this study the researcher examines this term in the Quran in its’ multiple forms- the present, the command and the past participle, in relation to both the context of the verse and reality. The study also links the Quranic term (Hope) to the teachings of Islam, as it is considered to be a devotional matter, a duty of faith, and a need imposed by reality, and whoever abandons hope is a sinner. The Almighty said: “Indeed, no one despairs of relief from Allah except the disbelieving people.” (surat Yousef, ayat 87)